A Preliminary Report on the Use of Bench-Top X-Ray Micro-Computerised Tomography to Study the Malpighian Tubules of the Overwintering Seven Spotted Ladybird Coccinella septempunctata L. (Coleoptera: Coccinellidae) - Duncan Bell; Lewis Woolnough; David Mortimore; Nick Corps; Diana M. Hudson; Mark K. Greco (Psyche: A Journal of Entomology)
The application of micro-CT scanning techniques on a small sample of “Seven-spot ladybirds” Coccinella septempunctata, collected in December 2009, identified an accumulation of material with a very high, relative X-ray attenuation value in the malpighian tubules of most but not all of the individuals sampled. The passage of metals such as cadmium in soil through a food chain to finally accumulate in high concentrations in ladybirds and lacewings has been previously reported. The identification of the dense material found in our sample of ladybirds, its origin, and the process by which it accumulates in, and is processed by, the malpighian tubules is the challenge ahead. The authors speculate that a straightforward means of monitoring levels of metallic pollutants in the environment might emerge.